Automatic Compliance Check of Window-to-Wall Ratio Software Embeded Intelligent Algorithms in Revit Modeling - Yan Xiu-ying; Wang Xiu-dong; Li Da-wei; Yan Xiulian; Fan Kai-xing; Liu Da-long (E3S Web of Conferences, 2022)
Window-to-Wall Ratio(WWR) is a crucial building envelope element that decides the air conditioning and lighting energy consumption in the building. Controlling WWR within a reasonable range is of great significance to building energy conservation. Due to the importance of WWR’s selection in Revit modeling, an automatic compliance check software in Revit Modeling is developed to ensure the WWR of Revit model within a reasonable range. The range is given in Design Standard for Energy Efficiency of Public Buildings (GB50189-2015,China). Based on the value range, the enumeration-based WWR compliance inspection software was developed in C# language and integrated into Revit to achieve compliance check on Revit model. Software testing was conducted for a certain office building in Shanghai, China. And Ecotect was used to analyze the thermal environment of unchecked model and checked model, respectively. The result shows that this software can automatically obtain the WWR of each facade of the current model, and determine whether it meets the range of the building location. When a facade does not meet the specification, it can be quickly and automatically adjusted to the appropriate range within the scope. By comparing the Ecotect thermal environment analysis results of unchecked and checked model, it is found that the heating and cooling loads are reduced after the model is checked with intelligent algorithms.